2009
DOI: 10.1097/ccm.0b013e3181a00a6a
|View full text |Cite
|
Sign up to set email alerts
|

In-hospital versus out-of-hospital pediatric cardiac arrest: A multicenter cohort study*

Abstract: Objectives To describe a large multicenter cohort of pediatric cardiac arrest (CA) with return of circulation (ROC) from either the in-hospital (IH) or out-of-hospital (OH) setting in order to determine if significant differences related to pre-event, arrest event, early post-arrest event characteristics and outcomes exist that would be critical in planning a clinical trial of therapeutic hypothermia (TH). Design Retrospective cohort study Setting Fifteen Pediatric Emergency Care Applied Research Network (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
140
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(148 citation statements)
references
References 46 publications
4
140
1
3
Order By: Relevance
“…However during reperfusion after CA, damaged brain mitochondria: (1) produce toxic-free radicals that directly attack vital cellular constituents; 22 (2) are at the convergence of critical cell death pathways such as apoptosis and necrosis; 14 and (3) are powerful mediators of inflammation. 23 Central to all three of these potentially pathologic mechanisms is the supraphysiologic generation of ROS, which can be used for oxidative signaling by selective enzymatic oxidation of CL followed by its hydrolysis and generation of lyso-CL and oxidized LA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However during reperfusion after CA, damaged brain mitochondria: (1) produce toxic-free radicals that directly attack vital cellular constituents; 22 (2) are at the convergence of critical cell death pathways such as apoptosis and necrosis; 14 and (3) are powerful mediators of inflammation. 23 Central to all three of these potentially pathologic mechanisms is the supraphysiologic generation of ROS, which can be used for oxidative signaling by selective enzymatic oxidation of CL followed by its hydrolysis and generation of lyso-CL and oxidized LA.…”
Section: Discussionmentioning
confidence: 99%
“…1 In survivors, functional correlates of neuronal injury emerge as the principal determinant of outcome. 2 An unfavorable neurologic outcome is seen in approximately 50% of the survivors when outcome is reported. 2 Supraphysiologic production of reactive oxygen species (ROS) after reperfusion is implicated as a key contributor to the pathophysiology of CA-induced neurologic injury.…”
Section: Introductionmentioning
confidence: 99%
“…Although the return of spontaneous circulation is seen in 30 to 65% of pediatric patients following a cardiac arrest (more commonly found in-hospital cardiac arrest) long-term survival with good neurological recovery that may be achieved in only a minority [158][159][160]. Common causes of death in nonsurvivors are brain death or neurological futility, particularly among patients who have an out-of-hospital arrest [161]. Neuroprotective strategies in pediatric cardiac arrest include induced hypothermia and extracorporeal cardiopulmonary resuscitation (ECPR).…”
Section: Advances In Cerebral Resuscitation In Childrenmentioning
confidence: 99%
“…The groundwork for this study has been well built. Three large, retrospective cohort studies that included patients from 15 hospitals affiliated with the Pediatric Emergency Care Applied Research Network have examined the outcome and identified risk factors associated with poor outcome for both in-hospital and out-of-hospital pediatric cardiac arrest [161][162][163][164][165][166][167][168][169][170][171]. Surveys from the United Kingdom and the United States have demonstrated both variability in the practice of cooling, and a widespread willingness and interest in a randomized controlled trial to study its use [172,173].…”
Section: Advances In Cerebral Resuscitation In Childrenmentioning
confidence: 99%
“…For the critical outcome of survival to hospital discharge, we identified very-low-quality evidence from 4 pediatric observational studies of IHCA [71][72][73][74] (downgraded for indirectness, inconsistency, and residual confounding) and very-low-quality evidence from 1 unpublished analysis of a study' s public dataset 75 (downgraded for serious risk of residual confounding) showing no benefit to the use of ECPR when compared with CPR without the use of ECMO (RR range, 0.64-1.63). We also identified low-quality evidence (downgraded for indirectness, inconsistency, and residual confounding) from a single pediatric study of IHCA 76 that showed benefit to ECPR when compared with CPR without the use of ECMO (OR, 2.5; 95% CI, 1.3-4.5; P50.007 in surgical cardiac diagnoses; OR, 3.8; 95% CI, 1.4-5.8; P50.011 in medical cardiac diagnoses).…”
Section: Consensus On Sciencementioning
confidence: 99%